Economic Feasibility Analysis of Off-Grid PV Systems for Remote Settlements in Bhutan - Thanarak, Prapita; Lhazom, Kezang (International Journal of Energy Economics and Policy, 2021)
Through rigorous rural electrification projects, over 99.97% of Bhutan's households now have access to electricity, which is predominantly generated from run-of-the-river hydropower plants. Despite this achievement, around 5% of the rural households still do not have access to electricity to meet their cooking load demands and, therefore, they extensively rely on firewood, LPG, and kerosene for cooking purposes. Apart from hydropower, penetration of other renewable sources such as solar and wind power in the country is negligible. Thus, an attempt was made to determine the investment costs of installing PV systems for off-grid households in remote settlements by studying their economic feasibility. The study shows that the initial cost of investment for an off-grid Solar Home System for a rural household is US$1.42 per Wp using polycrystalline PV modules and US$1.55 per Wp using monocrystalline PV modules. The average cost of installing SHS is determined to be US$ 2342.67 per household. The results of analyses indicate that standalone SHS for remote rural households is not financially viable with the current price of electricity supply in Bhutan. However, SHS provides a more cost-effective option than a grid-line extension, which is estimated to cost about US$ 6700 per household for the remaining off-grid settlements. Keywords: Rural electrification, off-grid, solar home system, PV system, economic analysis. JEL Classifications: C8, G0, Q4 DOI: https://doi.org/10.32479/ijeep.10665